Detection of opioid growth factor in Multiple Sclerosis Patients - Khamael Abdulla Taha; Mayada N. Iqbal; Gheyath Abd Ali Shalal (Journal of Techniques)
Multiple sclerosis (MS) is a recent prevalent central nervous system disease that affects the brain and spinal cord. It is assumed that it is an intermediate immune disorder in the central nervous system and is complex with incomplete etiology. Some research have confirmed that the Opioid growth factor(OGF), which was called chemically Enkephalin [Met5], is considered as a biomarker for the onset of MS. The purpose of this study was to look into the biomarker level of OGF and its correlation with  body mass index(BMI) among  patients with MS. A total number of 100 patients were diagnosed in two groups (54 early diagnosis of MS without treatment, 46 early diagnosis with treatment) according to McDonald criteria and 50 healthy control groups were included. All demographic data of the study samples  were recorded (age, gender), as well as  clinical data such as (BMI),and  level OGF(serum and saliva) estimated by ELISA method. The current study revealed that the   mean+SD of serum OGF in patients with multiple sclerosis for both groups(947.167 ± 134.262 ng/ml) was less concentrated than the control group (1046.642 ± 63.605 ng/ml) with a very large difference (P <0.01). While the mean concentration of OGF in saliva was (960.158 ± 91.684 ng/ml) for patients with multiple sclerosis (early diagnosis group without treatment  and the  treatment group), its concentration was higher than the control group (880.059 ± 87.700 ng/ml) with a large statistical significance (P <0.01). The current study showed  an important correlation between the body mass index and serum OGF level at (p = 0.022) in the early diagnosis group for multiple sclerosis patients with treatment,  , while in the early diagnosis group for multiple sclerosis patients without treatment, a very significant association was found between BMI and serum OGF level at (p = 0.009).   Interestingly, the current study showed that saliva biomarker (OGF) would be a good predictor for diagnosing MS.